If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3cos(x) + xsin(x) = 0 Multiply cos * x 3cosx + xsin(x) = 0 Multiply insx * x 3cosx + insx2 = 0 Solving 3cosx + insx2 = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1insx2' to each side of the equation. 3cosx + insx2 + -1insx2 = 0 + -1insx2 Combine like terms: insx2 + -1insx2 = 0 3cosx + 0 = 0 + -1insx2 3cosx = 0 + -1insx2 Remove the zero: 3cosx = -1insx2 Divide each side by '3osx'. c = -0.3333333333ino-1x Simplifying c = -0.3333333333ino-1x
| 29+(-35)= | | (5-w)/(w-5) | | 6x+100=700 | | x(x-6)=135 | | 2272=32(p+30) | | 6x^5=36 | | 8x-56=9x+90 | | 2272=32(6+30) | | 4/5x=9 | | 7-b=24 | | 6x-2=9(x+8) | | x^2-4x+12=3+2x | | 8-15n=5(-3n+2) | | 3x^2+4x=360 | | 120=.8*x | | (5+3i)(6-3i)= | | 10x+8y=4800 | | 8p-57=9p+10 | | 120=.8x | | -4x^2+29x-25=0 | | (sec^2)(x)=7 | | 47-12=5(x-2) | | x^3-3y^3-9z^3=0 | | x+3.5x=90 | | 1566=29(p+20) | | x+x+15+x+75=180 | | 14x=11x+33 | | x+18+3x=-20-3x-25 | | 14x=11x+34 | | 14x=11x+36 | | 14x=11x+41 | | 14x=11x+61 |